PENGEMBANGAN EKOWISATA AIR TERJUN PURUK KAWUK DI KABUPATEN MURUNG RAYA PROVINSI KALIMANTAN TENGAH - Superiadinata Superiadinata; Yetrie Ludang; Firlianty Firlianty (Jurnal Cakrawala Ilmiah, 2022)
Puruk Kawuk Waterfall is a natural waters located in Saripoi Village, Tanah Siang District, Murung Raya Regency. This study aims to (1) identify and analyze the potential for tourist attraction (ODTW) in the Puruk Kawuk Waterfall area, (2) formulate plans and strategies for ecotourism development in the Puruk Kawuk Waterfall area. Analysis of the potential of natural tourism objects and attractions using the Operational Area Analysis guideline - Natural Tourism Objects and Attractions (ADO-ODTWA) Director General of PHKA 2003. Ecotourism development plans and strategies for Puruk Kawuk Waterfall were prepared using SWOT analysis. The results of the study show that the assessment criteria for the Puruk Kawuk Waterfall (ATPK) area have a moderate classification, which indicates that this area has potential and is feasible to be developed, but has several obstacles and obstacles to be developed as an ecotourism destination